Music Students’ Perception Towards Music Distance Learning Education During COVID-19 Pandemic: Cross-Sectional Study in Jordan - Nsairat, Nedal; Fakhouri, Hussam N.; Alsawalqa, Rula; Hamad, Faten (International Journal of Interactive Mobile Technologies (iJIM), 2022)
During COVID-19 pandemic countries have faced various levels of COVID-19 infection rates, and millions of students are affected by changing the educational process. However, many music Schools have been faced with the challenge of dealing with a situation that necessitates emergency measures to continue the academic course in the midst of lock-downs and social distancing measures. Therefore, it is important to evaluate the effectiveness of online methods of learning and to decide their feasibility and appropriateness for music students. Thus, this research aimed to provide an analysis of Music Students’ Perception towered Music E-learning Education during COVID-19 Pandemic, to study the situation of musicians in COVID-19 and to study music Distance learning knowledge, attitudes and practices and to develop suggestions for solving the problems. A sample of (83) students from the music department in the University of Jordan completed a questionnaire. An online survey distributed The survey sought population and socio-economic information and information relating to electronic and online musical training; musical education during the COVID 19 pandemic; mental music assessments; and the skills, attitudes and practices of E-learning. Most respondents (76.2%) agreed that Distance learning is applicable in music department. While (54.2 %) of the respondents agreed Distance learning is a possible substitute for standard education. However, E-learning has actually been created as a modern way of improving the process of learning and improving learning performance.